Promoting the Efficiency and Stability of CsPbIBr2-Based All-Inorganic Perovskite Solar Cells through a Functional Cu2+Doping Strategy - Liu, P.; Yang, X.; Chen, Y.; Xiang, H.; Wang, Wei; Ran, R.; Zhou, W.; Shao, Zongping (AMER CHEMICAL SOC, 2020)
Although organic-inorganic halide perovskite solar cells (PSCs) have shown dramatically enhanced power conversion efficiencies (PCEs) in the last decade, their long-term stability is still a critical challenge for commercialization. To address this issue, tremendous research efforts have been devoted to exploring all-inorganic PSCs because of their intrinsically high structural stability. Among them, CsPbIBr2-based all-inorganic PSCs have drawn increasing attention owing to their suitable band gap and favorable stability. However, the PCEs of CsPbIBr2-based PSCs are still far from those of their organic-inorganic counterparts, thus inhibiting their practical applications. Herein, we demonstrate that by simply doping an appropriate amount of Cu2+ into a CsPbIBr2 perovskite lattice (0.5 at. % to Pb2+), the perovskite crystallinity and grain size are increased, the perovskite film morphology is improved, the energy level alignment is optimized, and the trap density and charge recombination are reduced. As a consequence, a decent PCE improvement from 7.81 to 10.4% is achieved along with an enhancement ratio of 33% with a CsPbIBr2-based PSC. Furthermore, the long-term stability of CsPbIBr2-based PSCs against moisture and heat also remarkably improved by Cu2+ doping. This work provides a facile and effective route to improve the PCE and long-term stability of CsPbIBr2-based all-inorganic PSCs.